Genotoxicity evaluation of zinc oxide nanoparticles in Swiss mice after oral administration using chromosomal aberration, micronuclei, semen analysis, and RAPD profile. (November 2017) - Srivastav, Anurag Kumar; Kumar, Akhilesh; Prakash, Jyoti; Singh, Dhirendra; Jagdale, Pankaj; Shankar, Jai; Kumar, Mahadeo
The expanded uses of zinc oxide nanoparticles (ZnO NPs) have grown rapidly in the field of nanotechnology. Thus, rising production of nanoparticles (NPs) increases the possible risks to the environment and occupationally exposed humans. Hence, it is indispensable to appraise the safety toxicity including genotoxicity for these NPs. In the present study, we have evaluated the genotoxic effect of ZnO NPs after oral administration to Swiss mice at dose levels of 300 and 2000 mg/kg body weight. These doses were administered for 2 days at 24 h apart. Chromosomal aberration (CA) and micronucleus tests were conducted following Organization for Economic Co-operation and Development guidelines. DNA damage was evaluated at 0, 24, 48, and 72 h posttreatment using a randomly amplified polymorphic DNA (RAPD) assay; additionally, semen analyses were also performed at 34.5 days post oral exposure. The reactive oxygen species (ROS), 8-oxo-2′-deoxyguanosine and CAs were increased ( p < 0.05) at the highest dosage (2000 mg/kg) of ZnO NPs compared to controls. Aberrant sperm morphology with reduced sperm count and motility were also present ( p < 0.05) in the high-dose group. Based on the RAPD assay, the genomic template stability within the high-dose group (<90%) was less than the controls (100%). The results suggested that ZnO NPs are mildly genotoxic in a dose-related manner and this toxicity were induced by generation of ROS.